Insight into the effects of environmental variables on the physicochemical characteristics and biochemical composition of green Arabica coffee - Markos Makiso Urugo; Yetenayet B. Tola; Biniam T. Kebede; Onwuchekwa Ogah (Beverage Plant Research)
This study conducted an in-depth assessment of green Arabica coffee bean samples sourced from diverse agro-ecologies in Ethiopia, focusing on the relationship between the beans' physicochemical characteristics and biochemical composition and their agro-ecological conditions. The study employs principal component analysis to elucidate the relationship between Arabica bean growing environmental conditions, physicochemical characteristics, and the biochemical composition of coffee beans from diverse Ethiopian agro-ecologies. The present findings reveal remarkable associations, particularly highlighting the impact of elevation in coffee-growing areas and the daily average temperature on key attributes such as hundred-bean weight, moisture content, crude fat content, and pH of the beans. Furthermore, the present study observed the intricate interplay between the beans' biochemical composition and diverse growing environmental variables. Except caffeine content, all other biochemical compositions of the beans exhibited significant associations with the prevailing environmental conditions during growth. Principal component analysis identifies variations in samples based on environmental variables, physicochemical, and biochemical composition. These findings highlight the complex impact of growing environmental conditions on the distinct quality of Arabica coffee beans across Ethiopian regions. For a comprehensive understanding of green Arabica beans from diverse agro-ecologies, future research should explore metabolites characterizing these beans based on their profiles.